2022
DOI: 10.5267/j.ijdns.2022.2.013
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the board of directors' performance in Jordan: The moderating effect of enterprise risk management

Abstract: This study aims to investigate the moderating effect of enterprise risk management on the relationship between the board of directors’ effectiveness on accounting and market performance in Jordan. The current study uses panel data of 684 firm-year observations, employed regression analysis and analysis of annual reports of 76 listed companies on the Amman stock exchange (ASE) from 2009 to 2017 covering 9 years. The findings of the hierarchical regression analysis showed that the enterprise risk management has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The finding is consistent with research conducted by Arnold et al . (2015) and Sakrabani and Teoh (2020) who also confirmed the moderating effect of ERM on firm performance and market performance (Shatnawi et al ., 2022). A practice of ERM by PHEIs in identifying treats and opportunities will enhance SA of PHEIs in making decisions, creating a competitive advantage to achieve success.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The finding is consistent with research conducted by Arnold et al . (2015) and Sakrabani and Teoh (2020) who also confirmed the moderating effect of ERM on firm performance and market performance (Shatnawi et al ., 2022). A practice of ERM by PHEIs in identifying treats and opportunities will enhance SA of PHEIs in making decisions, creating a competitive advantage to achieve success.…”
Section: Discussionmentioning
confidence: 79%
“…PHEIs' performance firm performance and market performance (Shatnawi et al, 2022). A practice of ERM by PHEIs in identifying treats and opportunities will enhance SA of PHEIs in making decisions, creating a competitive advantage to achieve success.…”
Section: Bdatc's Influence Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The suitable number of samples were calculated using Hwang et al’s (2016) suggestion of the, least, sample, size, to, be, 10 times higher than the, number, of, paths, leading, to the endogenous constructs (N = 60). In a similar line of recommendation, Hair et al (2019) stated that the respondents number, should, be, 8 times, that, of the number of the study, constructs ( Almaiah et al, 2022j ; Alrawad, Lutfi, Almaiah, et al, 2023 ; Shatnawi et al, 2022 ), based on which, the least size of the sample required was (N = 48).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that the level of creativity within individuals is related to three areas (expertise, creative thinking and motivation), these three factors are related and a development in one of the three areas can yield a strong impact on the other two [22], [23]. The results of a meta-analysis done in order to review the research on personality and creativity concluded that; creative people were found to be: "more autonomous, introverted, open to new experiences, normdoubting, self-confident, self-accepting, driven, ambitious dominant hostile and impulsive".…”
Section: Creativitymentioning
confidence: 99%